Transcriptome analysis reveals modulations in glycosylation profiles of the mucosal barrier and their potential interaction with gut microbiota in weaned piglets - Hao Cheng; Hao Li; Yujie Zhao; Kai Yang; Jing Wang; Bie Tan; Xiaokang Ma (Animal Nutrition)
The current study aims to investigate the potential interaction between glycosylation profiles of the Ningxiang breed (NX) and Western Duroc × Landrace × Yorkshire breed (DLY) weaned piglets, and their characteristic microbes, employing integrated analyses of transcriptomics and metagenomics. Twenty-four (12 NX and 12 DLY) at 28 days of age were transported into an experimental house and fed the same weaned piglet diet. The trail period was 7 days. Results revealed that the NX piglets had a higher growth-to-feed ratio, body weight gain scale, and lower pathological score of intestinal injury compared with the DLY piglets (P < 0.01). DLY piglets displayed elevated mRNA expression levels of MUC2 and MUC5AC in colonic mucosal tissue than NX piglets (P < 0.05). Within the O-linked glycosylated differentially expressed genes (DEGs), FNTA, GALNT18, POMGNT1, POMGNT2, and POMT1 were significantly upregulated in DLY piglets relative to NX piglets (P < 0.05). Conversely, C1GALT2, GALNT1, KMT2C, and OGT were significantly downregulated in DLY piglets compared to NX piglets (P < 0.05). The KMT2C gene was hardly expressed in the transcriptome of DLY piglets. At the phylum taxonomic level, NX piglets had a higher abundance of Firmicutes, while DLY piglets had a higher abundance of Proteobacteria. At the genus taxonomic level, NX piglets had a higher abundance of Lactobacillus, whereas DLY piglets had a higher abundance of Collinsella, Enterococcus and Escherichia. The results of the correlation between intestinal differential bacteria and O-chain glycosylated DEG showed that C1GALT2, GALNT1 and KMT2 were associated with Lactobacillus_pontis showed a positive correlation (R = 0.67). Through comparative analysis of differentially glycosylated genes and their associated functions, this study highlights the potential role of reduced expression of GALNT1 and KMT2C genes, involved in O-linked protein and glycan reactions, in impairing the intestinal barrier function of DLY piglets. Furthermore, members of the Lactobacillus and Prevotella genera may actively contribute to the regulation of piglet colon glycosylation profiles.